Newborn Screening Today and Tomorrow: A Brief Report from the International Primary Immunodeficiencies Congress - Leire Solis; Samya Van Coillie; James R. Bonham; Fabian Hauck; Lennart Hammarström; Frank J. T. Staal; Bruce Lim; Martine Pergent; Johan Prévot (International Journal of Neonatal Screening, 2024)
This article presents the report of the session on “Newborn Screening for Primary Immunodeficiencies—Now What?” organised during the International Primary Immunodeficiency Congress (IPIC) held in November 2023. This clinical conference was organised by the International Patient Organisation for Primary Immunodeficiencies (IPOPI), the global patient organisation advocating for primary immunodeficiencies (PIDs) in patients. The session aimed at exploring the advances in newborn screening (NBS) for severe combined immunodeficiency, starting with the common practice and inserting the discussion into the wider perspective of genomics whilst taking into consideration the ethical aspects of screening as well as incorporating families and the public into the discussions, so as to ensure that NBS for treatable rare disorders continues to be one of the major public health advances of the 20th century.